GAYA HIDUP KOMUNITAS PENCINTA BUDAYA JEPANG DI KALANGAN MAHASISWA UNNES (STUDI KASUS PADA KOMUNITAS JAICO) (Solidarity: Journal of Education, Society and Culture, 2013)
Community lover of Japanese cultureis one of the teenagers gathering place with adistinctive and unique appearance that is different from other communities. With the appearance of its members a unique, asymmetrical haircuts and clothest end to bebrightly colored with trinkets attached here and there,making them very easy to recognize.Japan Independent Community (Jaico) is one of the community who are lovers of Japanese culture at Semarang State University (UNNES). Jaico member UNNES students and outsiders who have the same interests and hobbies that Japanese culture. The existence of such communities JaicoUNNES able to attract students to join in it. Especially for those who basically do like the Japanese culture. With qualitative research methods. And located in UNNES, the author would like to know the background of students attend Japanese pop culture lifestyle, their motivation to join the community of lovers of Japanese culture, and community lifestyle lovers of Japanese culture itself .Most of them follow the Japanese pop culture because it is unique and interesting. The presence of media and peer influence in motivating students of the community to join. They follow the lifestyle of Japanese pop culture that are considered interesting and different look of the hairstyles and clothing styles are in the adoption of Japanese artists.